A construção de saberes docentes dos professores indígenas do ensino fundamental II da Comunidade Canauanim-RR - Lima, Claudinero Reis de (2022)
The present work has the main objective of investigating the perspectives of teachers who work in the initial grades of an indigenous school in Roraima, in order to identify, based on essential documents of indigenous school education, the desired capacities for the profile of an indigenous teacher. The research is configured as a case study based on a qualitative approach, having as locus the Escola Estadual Tuxaua Luiz Cadete, located in the Canauanim Indigenous Community, in the municipality of Cantá, state of Roraima. It is in this educational establishment that the investigated subjects work: indigenous teachers from the 1st to the 5th year of Elementary School I. In order to achieve the proposed objectives, individual interviews with the research subjects will be applied as an instrument for data collection. , from a semi-structured script. The interview responses will be subjected to coding and categorization, according to the Content Analysis method, resulting in the following analysis categories: a) length of experience and form of admission; b) type of training; c) type of education; d) purposes of school education; f) mastery and use of the mother tongue; g) dialogue with the community; h) identification with the community; i) relationship with indigenous productions; j) application of indigenous knowledge in classes; h) training offered. Finally, the various specific objectives outlined for this research will help to verify whether the perspectives of these teachers establish, in fact, a dialogue with indigenous school education. The impact of this research is to help better identify the challenges faced by indigenous teachers in their pedagogical work to promote intercultural education.